Cooperation is not rewarded by friendship, but generous and selfish students repel each other in social networks - Flóra Samu; Simone Piras; Simone Righi; Marco Setti; Károly Takács (PLoS ONE, 2025)
Humans cooperate across various contexts, despite the individual costs involved. Cooperation and prosocial behavior may persist because these costs are offset by reputation and other social benefits. Specifically, cooperators and prosocial individuals may receive more friendship nominations and be less likely to face exclusion or avoidance. We test whether such beneficial network dynamics are present in a unique dataset of twenty primary school classes in northern Italy. Cooperation and social preferences of 420 students in grades 4 and 5 were measured with incentivized social dilemma games, and the social network of the entire classroom was traced on two subsequent occasions. We modeled the dynamics of friendship and negative ties with Stochastic Actor-Oriented Models, and conducted a meta-analysis of the results. Our key finding is that, while we do not observe evidence of homophily based on social preferences in friendship nominations - and being prosocial does not lead to receiving more friendship nominations, individuals are significantly more likely to direct negative tie nominations toward peers who made different offers in the dictator game. These results suggest that social network dynamics support cooperation not by rewarding prosocial behavior with friendship, but through repulsion between prosocial and selfish students.